Fertility preservation in female cancer sufferers: (only) a moral obligation?. (4th July 2022) - Zaami, Simona; Stark, Michael; Signore, Fabrizio; Gullo, Giuseppe; Marinelli, Enrico
Abstract: Purpose: Advances in cancer diagnostics and therapeutics have thankfully led to high numbers of young cancer survivors, although some interventions may sometimes threaten fertility. The authors aimed to assess how evidence-based oncofertility counselling can be adequately fulfilled for the sake of female cancer patients, in light of its complexities and multidisciplinary nature, which require thorough counselling and consent pathways. Materials and Methods: A search has been conducted in the databases PubMed/MEDLINE, Web of Science, Scopus, EMBASE and Google Scholar via search strings such as fertility preservation, reproductive counselling, oncofertility, cancer survivors, in order to identify relevant meaningful sources spanning the 2010–2021 period. Results: Counselling needs to be implemented in compliance with international guidelines, so as to avoid medicolegal repercussions. Albeit fertility preservation is supported by most health care institutions, actual conditions at health care facilities often reflect several lingering difficulties in the oncofertility process. Oncofertility counselling should foster access to fertility preservation procedures. To best serve that purpose, it should be implemented in a manner consistent with ethical and legal standards, so that patients can make an informed decision based on comprehensive and relevant data. Conclusions: Counselling needs to be rooted in a close cooperation of oncologists, reproductive endocrinologists, mental health counsellors and clinical researchers. The provision of oncofertility services is grounded in the moral obligation to uphold individual autonomy, which is essential in a free society, unless the exercise thereof could pose a risk to the children conceived or to others.